Redesain Logo UMKM “Weave” - Firaghaida Effendi; Restu Ismoyo Aji (Journal of Creative Student Research, 2023)
Weave or Witrove, before the brand name change, was a fashion crafting enterprise specializing in designing items like bags and wallets crafted from natural materials, particularly water hyacinth. Apart from producing fashion products for sale, Weave also contributed to controlling the growth of water hyacinths in the vicinity to prevent ecological damage and other related issues. However, the Weave brand lacked a strong visual identity. Therefore, a logo redesign was necessary to establish a distinctive brand identity compared to other fashion brands and to enhance Weave's visibility in promoting its products through media channels. Data collected for this redesign involved interviews and observations, which were then analyzed using a qualitative descriptive data . This research encompassed several stages to create a visual identity in the form of a logo.